Red faces all round. - Anslow, Mark (Ecologist, 2009)
The author opines regarding the computer hacking and posting of emails exchanged by climate scientists at the University of East Anglia. The author believes that ensuing media coverage was to be expected, but that it doesn't undermine the science of climate change. The author believes that the emails would have been similarly publicized even if they had been written by climate skeptics.